Whole-Blood Transcriptional Signatures Composed of Erythropoietic and NRF2-Regulated Genes Differ Between Cerebral Malaria and Severe Malarial Anemia. (28th July 2018) - Nallandhighal, Srinivas; Park, Gregory S; Ho, Yen-Yi; Opoka, Robert O; John, Chandy C; Tran, Tuan M
Abstract: Background: Among the severe malaria syndromes, severe malarial anemia (SMA) is the most common, whereas cerebral malaria (CM) is the most lethal. However, the mechanisms that lead to CM and SMA are unclear. Methods: We compared transcriptomic profiles of whole blood obtained from Ugandan children with acute CM (n = 17) or SMA (n = 17) and community children without Plasmodium falciparum infection (n = 12) and determined the relationships among gene expression, hematological indices, and relevant plasma biomarkers. Results: Both CM and SMA demonstrated predominantly upregulated enrichment of dendritic cell activation, inflammatory/Toll-like receptor/chemokines, and monocyte modules, but downregulated enrichment of lymphocyte modules. Nuclear factor, erythroid 2 like 2 (Nrf2)-regulated genes were overexpressed in children with SMA relative to CM, with the highest expression in children with both SMA and sickle cell disease (HbSS), corresponding with elevated plasma heme oxygenase-1 in this group. Erythroid and reticulocyte-specific signatures were markedly decreased in CM relative to SMA despite higher hemoglobin levels and appropriate increases in erythropoietin. Viral sensing/interferon-regulatory factor 2 module expression and plasma interferon-inducible protein-10/CXCL10 negatively correlated with reticulocyte-specific signatures. Conclusions: Compared with SMA, CM is associated with downregulation of Nrf2-related and erythropoiesis signatures by whole-blood transcriptomics. Future studies are needed to confirm these findings and assess pathways that may be amenable to interventions to ameliorate CM and SMA. Abstract : Whole-blood transcriptional profiling revealed downregulation of erythropoietic and Nrf2-regulated signatures in children with cerebral malaria relative to children with severe malarial anemia. Viral sensing/interferon-regulatory factor 2 module expression and plasma interferon-inducible protein-10/CXCL10 negatively correlated with reticulocyte-specific signatures, suggesting interferon-mediated erythropoietic suppression.